Mediación pedagógica como instrumento de comunicación y convivencia - Gallo Bedoya, Linda (Universidad Santiago de Cali, 2020)
This article presents some results of the research Sowing in Diversity Contexts, carried out in the area of the community of Guachené, in the department of Cauca, in Colombia. These communities were Naza, Guachené afro descendants, and people from Universidad Francisco José de Caldas's campus community. This paper focuses on de measurements done in Guachené, Cauca, Colombia. In this research was studied the community ́s coexistence, the recognition of cultural traditions that are inherited from generation through generation, and multiple factors that give life to cultural identity. The framework included various pedagogical mediations raised from the art, such as: oral narration of stories, traditional songs, the recovery of memory through dialogue, and finally, the approximation to the methodology of talking maps. The result of this research shows how participatory learning is important for the processes of identity construction, replacement of dialogue in community, the need for cultural memory recovery, and the community ́s empowerment through participatory maps.